Pelvic Inflammatory Disease Caused by Salmonella Bacteremia: Report of Two Cases - Özlem Özdeğirmenci; Fulya Kayıkçıoğlu; Gönül Aksu; Muzeyyen Güneş; Ali Haberal (Medical Network, 2011)
Pelvic inflammatory disease (PID) is one of the most serious complications of the sexually transmitted diseases. The most important step in early diagnosis is a high index of clinical suspicion. In this report, we document two cases of PID due to Salmonella bacteremia.